Airway inflammation and hyperresponsiveness in subjects with respiratory symptoms and normal spirometry. Issue 3 (23rd March 2023) - Boulet, Louis-Philippe; Boulay, Marie-Ève; Côté, Andréanne; FitzGerald, J. Mark; Bergeron, Céline; Lemière, Catherine; Lougheed, M. Diane; Vandemheen, Katherine L.; Aaron, Shawn D.
Background: Subjects without a previous history of asthma, presenting with unexplained respiratory symptoms and normal spirometry, may exhibit airway hyperresponsiveness (AHR) in association with underlying eosinophilic (type 2 (T2)) inflammation, consistent with undiagnosed asthma. However, the prevalence of undiagnosed asthma in these subjects is unknown. Methods: In this observational study, inhaled corticosteroid-naïve adults without previously diagnosed lung disease reporting current respiratory symptoms and showing normal pre- and post-bronchodilator spirometry underwent fractional exhaled nitric oxide ( F ENO ) measurement, methacholine challenge testing and induced sputum analysis. AHR was defined as a provocative concentration of methacholine causing a 20% fall in forced expiratory volume in 1 s (PC20 ) <16 mg·mL −1 and T2 inflammation was defined as sputum eosinophils >2% and/or F ENO >25 ppb. Results: Out of 132 subjects (mean±sd age 57.6±14.2 years, 52% female), 47 (36% (95% CI 28–44%)) showed AHR: 20/132 (15% (95% CI 9–21%)) with PC20 <4 mg·mL −1 and 27/132 (21% (95% CI 14–28%)) with PC20 4–15.9 mg·mL −1 . Of 130 participants for whom sputum eosinophils, F ENO or both results were obtained, 45 (35% (95% CI 27–43%)) had T2 inflammation. 14 participants (11% (95% CI 6–16%)) had sputum eosinophils >2% and PC20 ≥16 mg·mL −1, suggesting eosinophilic bronchitis. The prevalence of T2 inflammation was significantly higher in subjects with PC20 <4 mg·mL −1 (12/20 (60%)) than in those with PC20 4–15.9 mg·mL −1 (8/27 (30%)) or ≥16 mg·mL −1 (25/85 (29%)) (p=0.01). Conclusions: Asthma, underlying T2 airway inflammation and eosinophilic bronchitis may remain undiagnosed in a high proportion of symptomatic subjects in the community who have normal pre- and post-bronchodilator spirometry. Asthma and eosinophilic bronchitis may remain undiagnosed in a significant number of subjects reporting respiratory symptoms but with normal spirometry; identification of these subjects should be emphasised to improve their management http://bit.ly/3ToeCrv